EU terrorism situation and trend report TE-SAT / EUROPOL / 2010 (EU terrorism situation and trend report TE-SAT, 2010)
The EU terrorism situation and trend report (TE-SAT) contains basic facts and figures regarding terrorist attacks, arrests and activities in the EU. The TE-SAT is based mainly on information contributed by EU Member States resulting from criminal investigations into terrorist offences. Terrorism and related phenomena in the EU are summarised in terms of both quantity and quality, and trends are identified for the period 2007 to 2009.